2009
DOI: 10.1080/10253890802137437
|View full text |Cite
|
Sign up to set email alerts
|

Chronic restraint stress impairs T-cell immunity and promotes tumor progression in mice

Abstract: Long-term exposure to stressful situations can affect the immune system. The T-cell response is an important component of anti-tumoral immunity. Hence, impairment of the immune function induced by a chronic stressor has been postulated to alter the immunosurveillance of tumors, thus leading to a worse neoplastic prognosis. Here, we show that chronic restraint stress affects T-cell mediated immunity in mice. This was evidenced by a decrease of mitogen-induced T-cell proliferation, a reduction in CD4(+)T lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 43 publications
1
53
1
Order By: Relevance
“…Some investigators suggested a dichotomy between the impact of acute and chronic stress, namely that chronic stress suppresses immunity and reduces resistance to diseases, while acute stress enhances immunity and disease resistance [25,26]. However, several acute stressors were actually shown to suppress various immune indices, including peripheral levels of NK activity and Th1 cytokine levels [27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators suggested a dichotomy between the impact of acute and chronic stress, namely that chronic stress suppresses immunity and reduces resistance to diseases, while acute stress enhances immunity and disease resistance [25,26]. However, several acute stressors were actually shown to suppress various immune indices, including peripheral levels of NK activity and Th1 cytokine levels [27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Stress is a known risk factor for human diseases, such as autoimmune diseases, infectious diseases and cancer [8,9] . Epidemiologic and experimental animal studies have shown that stress may alter tumor growth [10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…This effect on proinflammatory interleukins is specific to the type of brain structure studied and the type of stress applied (Plata-Salaman et al, 2000). As regards the adaptive immune response, it has been shown, for example, that chronic stress alters the balance of Th1 and Th2 lymphocytes (Frick et al, 2009). Social stress may also trigger a decrease in the proliferative capacity of splenic T lymphocytes and the proliferative capacity of NK cells (Beitia et al, 2005;Stefanski & Ben-Eliyahu, 1996).…”
Section: Studies In Animalsmentioning
confidence: 99%